2019
DOI: 10.1111/liv.14267
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic vascularization and functionalization of implantable bio engineered hepatic tissue alleviates liver injury in rats

Abstract: Background The challenge of using bioengineered liver lies in sustaining the quantity of high‐quality hepatocytes and the vasculature for blood perfusion. We characterized the heparinization of a porcine decellularized liver scaffold (DLS) as a carrier to support hepatocyte angiogenesis, thereby developing functional and vascularized hepatic tissue useful to treat liver injury. Method The porcine DLS was obtained by the removal of cellular components and then subjected to heparinization by the end‐point attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…The scaffold functionality was observed 48 and 72 h post-transplantation decreasing aspartate transaminase (AST) levels and increasing albumin (ALB) levels in recipient animals’ serum. Li et al 131 transplanted bioengineered hepatic tissues in the omentum majus of recipient mice treated with CCl 4 7 days before transplantation. The authors observed that recellularized liver graft was able to improve the recipient’s serological parameters (decreasing AST, total bilirubin levels, and increasing albumin ALB levels) and also ameliorated native liver fibrogenesis.…”
Section: Animal Models To Test Ex Vivo Bioengineered Liver Functional...mentioning
confidence: 99%
See 1 more Smart Citation
“…The scaffold functionality was observed 48 and 72 h post-transplantation decreasing aspartate transaminase (AST) levels and increasing albumin (ALB) levels in recipient animals’ serum. Li et al 131 transplanted bioengineered hepatic tissues in the omentum majus of recipient mice treated with CCl 4 7 days before transplantation. The authors observed that recellularized liver graft was able to improve the recipient’s serological parameters (decreasing AST, total bilirubin levels, and increasing albumin ALB levels) and also ameliorated native liver fibrogenesis.…”
Section: Animal Models To Test Ex Vivo Bioengineered Liver Functional...mentioning
confidence: 99%
“…As far as we know, a few descriptions of ex vivo bioengineered liver transplantation in the recipient liver disease model were published. 129 131 Probably, it can be explained by the difficulty of reaching long-term survival taxes after transplantation. A substantial number of animal models with liver disease already have a high mortality rate during the time of induction, which hinders their surgical performance resulting in short-term survival taxes.…”
Section: Animal Models To Test Ex Vivo Bioengineered Liver Functional...mentioning
confidence: 99%
“…The recellularization of DLS has led to the construction of functional bioengineered livers in vitro. 3,4 However, the vascularization of DLS remains a major challenge in engineering a transplantable liver. Constructing a functional vasculature in DLS is crucial for nutrient and oxygen delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Decellularized liver scaffold (DLS) with intact vascular networks and extracellular matrices (ECMs) is a promising material for engineering functional organs. The recellularization of DLS has led to the construction of functional bioengineered livers in vitro. , However, the vascularization of DLS remains a major challenge in engineering a transplantable liver. Constructing a functional vasculature in DLS is crucial for nutrient and oxygen delivery.…”
Section: Introductionmentioning
confidence: 99%
“…These forms are fabricated using digested ECM, homogenized ECM, or ECM ink, respectively. These ECM forms could be used for cell delivery, but they have relevant limitations, mainly due to the additional loss of biochemical components during the digestion and fabrication processes [97,[109][110][111][112][113][114][115][116].…”
Section: Bioengineered Liver Scaffolds and Their Transplantationmentioning
confidence: 99%